Analisis Motivasi Belajar Siswa Kelas X IPS 8 Padamateri Kerajaan Kerajaan Islam di Indonesia di SMAN 2 Pontianak - Fadilla, Fitrah; Rustiyarso, Rustiyarso; Mirzachaerulsyah, Edwin (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the motivation of learning history of students in class X IPS 8 on the material of Islamic Kingdoms in Indonesia at SMA N 2 Pontianak, while the research method used is descriptive with a qualitative research form. The source of data in this study were students of class XIPS8. Data collection techniques with observation, interviews and documentation, the data collection tools are observation guidelines, interview guidelines and documentation. Data analysis techniques use data reduction, data presentation and data summarization. The results showed that the intrinsic and extrinsic motivation to learn history of students in class X IPS 8 SMA N2 Pontianak on the material of the kingdom of the Islamic kingdom in Indonesia there are two indicators, namely; 1) intrinsic motivation to learn history of students in class X IPS 8 on the material of the kingdom of the Islamic kingdom in Indonesia lacks desire, desire and encouragement as well as hopes and ideals in learning the history of the material of the kingdom of the Islamic kingdom in Indonesia. 2) extrinsic learning motivation of students in class X IPS 8 on the material of the kingdom of the Islamic kingdom in Indonesia, shows that awards, interesting activities in learning, and a conducive learning atmosphere still make students less motivated in terms of learning the history of the material of the Islamic kingdom in Indonesia. It can be said that the results of the study show that the motivation to learn history of students in class x ips 8 on the material of the kingdom of the Islamic kingdom in Indonesia SMAN 2 pontianak is low